2021
DOI: 10.1002/ccr3.3731
|View full text |Cite
|
Sign up to set email alerts
|

Severe SARS‐CoV‐2 infection presenting with acute kidney injury and diabetic ketoacidosis complicated by pancreatitis in a 53‐year man with hypertension

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The detailed characteristics of the included studies are shown in Table 1 . Among the included studies, 11 reported DKA and COVID-19 in children [ 8 , 11 , 22 , 30 , 34 , 44 , 45 , 56 , 61 , 66 , 72 ], 56 reported DKA and COVID-19 in adults [ 9 , 10 , 12 21 , 23 , 25 29 , 31 33 , 35 43 , 46 55 , 57 – 60 , 62 65 , 67 71 , 73 75 ], and only 1 study reported DKA and COVID-19 in both children and adults [ 24 ]. There were 54 case report [ 8 12 , 14 , 16 , 17 , 19 23 , 25 27 , 29 42 , 44 51 , 53 58 , 60 , 61 , 64 , 66 , 67 , 69 , 71 , 72 , 74 , 75 ], 10 case series [ 13 , 15 , 28 , 43 , 58 , 59 , 62 , …”
Section: Resultsmentioning
confidence: 99%
“…The detailed characteristics of the included studies are shown in Table 1 . Among the included studies, 11 reported DKA and COVID-19 in children [ 8 , 11 , 22 , 30 , 34 , 44 , 45 , 56 , 61 , 66 , 72 ], 56 reported DKA and COVID-19 in adults [ 9 , 10 , 12 21 , 23 , 25 29 , 31 33 , 35 43 , 46 55 , 57 – 60 , 62 65 , 67 71 , 73 75 ], and only 1 study reported DKA and COVID-19 in both children and adults [ 24 ]. There were 54 case report [ 8 12 , 14 , 16 , 17 , 19 23 , 25 27 , 29 42 , 44 51 , 53 58 , 60 , 61 , 64 , 66 , 67 , 69 , 71 , 72 , 74 , 75 ], 10 case series [ 13 , 15 , 28 , 43 , 58 , 59 , 62 , …”
Section: Resultsmentioning
confidence: 99%
“…The disease severity is more pronounced in patients with comorbidities [ 1 , 2 ]. The presentation of SARS-CoV-2 infection is mainly with respiratory symptoms, but other major organ involvement liver, kidney, and pancreas are also seen [ 3 , 4 ]. Vaccines are the main preventive measures for containing the SARS-CoV-2 epidemic.…”
Section: Introductionmentioning
confidence: 99%
“… 3 In published literature, numerous cases of COVID-19 complicated with AP have been reported ( Table 1 ). 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 However, no robust causative relationship has been established between them.…”
Section: Introductionmentioning
confidence: 99%